A conventional multiplex PCR for the detection of four common soil-transmitted nematodes in human feces : development and validation - Hassan, N.A.; Noor Badi, F.A; Mohd-Shaharuddin, N.; Wan Yusoff, W. S; Lim, Y.A.L.; Chua, K.H.; Sidi Omar, S.F.N; Chang, L.Y.; Majid, H. A; Romano, Ngui (The Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2022)
Soil-transmitted helminth (STH) infections, mainly caused by Ascaris lumbricoides, Trichuris trichiura, and hookworms, are among the most common intestinal parasites that infect humans. The infections are widely distributed throughout tropical and subtropical countries, including Malaysia, particularly in underprivileged communities. Microscopic and culture techniques have been used as a gold standard for diagnostic techniques. However, these methods yield low sensitivity and specificity, laborious and time-consuming. Therefore, simple, rapid, and accurate alternative methods are needed for the simultaneous detection of STH infections. Although advanced technologies such as real-time multiplex PCR have been established, the use of this technique as a routine diagnostic is limited due to the high cost of the instrument. Therefore, a single-round multiplex conventional PCR assay for rapid detection of four STH species in the fecal sample was developed in this study. To perform the single-round multiplex PCR, each pair of species-specific primers was selected from target genes, including Ancylostoma duodenale (Internal Transcribed Spacer 2; accession No. AJ001594; 156 base pair), Necator americanus (ITS 2; accession No. AJ001599; 225 base pair), Ascaris lumbricoides (Internal Transcribed Spacer 1; accession No. AJ000895; 334 base pair) and Trichuris triciura (partial ITS 1, 5.8s rRNA and partial ITS 2; accession No. AM992981; 518 base pair). The results showed that the newly designed primers could detect the DNA of STH at low concentrations (0.001 ng/μl) with no cross-amplification with other species. This assay enables the differentiation of single infections as well as mixed infections. It could be used as an alternative and is a convenient method for the detection of STHs, especially for the differentiation of N. americanus and A. duodenale.